Implementation of STEM-Oriented MEA learning model to improve computational thinking skills of learners - Suryani, Karmila; Khairudin, Khairudin; Rahmadani, Ade Fitri; Widyastuti, Rini; Winsa, Larasati (Journal of Science and Education (JSE), 2024)
Low computational thinking skills cause students to have difficulty solving problems. This study aims to analyze whether there is an increase in students' CT abilities using the STEM-oriented MEA model with conventional learning. The research method is an experiment using an experimental group of 30 students and a control class of 32 students. The research instrument uses questionnaires and rubrics to assess students' CT abilities. The results of the T-test analysis used are Equal variances not assumed, which is 0.000 (Sig. (2-tailed)) > 0.05 means There is an increase in student's CT abilities using the STEM-oriented MEA model with conventional learning, so There is an increase in student's CT abilities using the STEM-oriented MEA model with conventional learning. Thus, there is an increase in the ability of students to think computationally using the STEM-oriented MEA model with conventional learning.